The minimum vital income in the light of the European Union Law and the international Social Security treaties in force in Spain - Sánchez-Rodas Navarro, Cristina (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The Minimum Vital Income and the minimum autonomic incomes have undeniable similarities attending to their objectives and material scope, being the most remarkable difference that the first one is legally qualified as a non-contributory social security benefit subject to income test. There is no doubt that the Minimum Vital Income is included into the material scope of application of Regulation 883/2004 on the coordination of social security systems. Therefore it is exportable to the States where European Union law is applied. But at the same time it can also be qualified as a social advantage under Regulation 492/2011 and as a social assistance benefit for the purposes of Directive 2004/38. With respect to the application of the International Social Security Treaties in force in Spain to the Minimum Vital Income, there may be a dichotomy between administrative practice and the material scope of those Treaties.
Keywords: non-contributory social security benefit; social assistance; Minimum Vital Income; European Pillar of Social Rights